A mini-review on mobile manipulators with Variable Autonomy - Contreras, Cesar Alan; Rastegarpanah, Alireza; Chiou, Manolis; Stolkin, Rustam (Frontiers in Robotics and AI, 2025)
This paper presents a mini-review of the current state of research in mobile manipulators with variable levels of autonomy, emphasizing their associated challenges and application environments. The need for mobile manipulators in different environments, especially hazardous ones such as decommissioning and search and rescue, is evident due to the unique challenges and risks each presents. Many systems deployed in these environments are not fully autonomous, requiring human-robot teaming to ensure safe and reliable operations under uncertainties. Through this analysis, we identify gaps and challenges in the literature on Variable Autonomy, including cognitive workload and communication delays, and propose future directions, including whole-body Variable Autonomy for mobile manipulators, virtual reality frameworks, and large language models to reduce operators’ complexity and cognitive load in some challenging and uncertain scenarios.